STANDARISASI KOMPETENSI BAHASA ARAB BAGI CALON SARJANA PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI - Muhbib Abdul Wahab; Aziz Fahrurrozi; Tulus Musthafa; Syamsul Arifin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aims to explore, analyze, and formulate the standard of Arabic competence for prospective graduates of S1 in UIN Jakarta and UIN Yogyakarta related to four language skills: listening, speaking, reading, and writing based on the assessment of Arabic language requirements and standards. This research used qualitative approach. In collecting the data, the researchersplayed themselve as